Analisis Upaya Pencapaian Indikator Kapitasi Berbasis Pemenuhan Komitmen Pelayanan (KBPKP) di Puskesmas Rumbai Kota Pekanbaru - widodextrosa widodextrosa; Irwan Muryanto; Novita Rany; Ahmad Hanafi; Adliana Puspasari (Jurnal Kesehatan Komunitas, 2020)
Capitation Based on Service Commitment Fulfillment (KBPKP) is an adjustment to the capitation rate based on the results of an agreed assessment of individual health service indicators in the form of a commitment to First Level Health Facilities (FKTP) services in order to increase the efficiency and effectiveness of health service delivery in FKTPs. The achievement of the target indicators for the Capitation Based on Service Commitment Fulfillment (KBPKP) at Puskesmas Rumbai Pekanbaru has not been satisfactory. Throughout 2019, most of the KBPKP indicators were in unsafe conditions with a capitation payment range ranging from 90% - 95%. The research objective was to analyze the efforts to achieve the Capitation indicator based on Service Commitment Fulfillment (KBPKP) at the Rumbai Public Health Center in Pekanbaru City in 2019. The method of selecting informants used snowball sampling. Data source qualified and able to present opinions well. The informants in this study were flexible according to the adequacy and suitability of the study. The results showed that the efforts to achieve the Capitation indicators based on the Service Commitment Fulfillment (KBPKP) at Puskesmas Rumbai, Pekanbaru City were not optimal. Commitment to achieve indicator numbers is still lacking. The strategy that has been made is not clear, therefore there is no effort to formulate a clear, structured and systematic strategy. Organizational structure is not followed by a description of the main tasks and functions so that supervision becomes weak, program holder officers do not focus on realizing the plan for achieving the service commitment based capitation indicator (KBPKP) that has been determined as a result efforts to achieve the KBPKP indicator are difficult to realize. It is recommended that efforts be made to make SOPs, a comprehensive, measurable, systematic plan, formulate the main tasks and functions for officers assigned as personnel to realize the target indicators that have been set so that coordination and control of actions in realizing the KBPKP indicators can be carried out properly.